2014
DOI: 10.1177/2153368714542007
|View full text |Cite
|
Sign up to set email alerts
|

Racial Crime Stereotypes and Offender Juvenility

Abstract: Recent theoretical advancements of the racial threat model of punitiveness suggest that because youthful offending has driven crime trends in recent decades, and because racially exclusive conceptions of childhood have historically structured public opinion on juvenile justice, Black criminal stereotypes may be especially consequential for attitudes toward juvenile punishments. Building on this work, the current study uses national survey data to examine whether the strength of the relationship between Black c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Future research may also focus on the knowledge and practices of justice system actors who represent and advocate for youth in the justice system, who are uniquely positioned to educate and inform youth and their families about collateral consequences (Pinard, 2006). Additionally, given the salient issues of racial and ethnic disparities in the juvenile justice system (Pickett, Welch, Chiricos, & Gertz, 2014), future research should examine more nuanced differences in the public's perceptions of collateral consequencesboth how participants' race may impact perceptions and how the public's attitudes may differ depending on the race of youth in the justice system.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Future research may also focus on the knowledge and practices of justice system actors who represent and advocate for youth in the justice system, who are uniquely positioned to educate and inform youth and their families about collateral consequences (Pinard, 2006). Additionally, given the salient issues of racial and ethnic disparities in the juvenile justice system (Pickett, Welch, Chiricos, & Gertz, 2014), future research should examine more nuanced differences in the public's perceptions of collateral consequencesboth how participants' race may impact perceptions and how the public's attitudes may differ depending on the race of youth in the justice system.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Although highlighting racial disparities in these studies did not have the intended effect, it does appear that race still plays a role in crime control policy preferences. Building on related research (Chiricos et al, 2004;Pickett, Welch, et al, 2014), findings from Study 1 illustrate how the perceived association between race and crime influences the public's policy preferences. Participants who believe violent crime is more of a "Black" phenomenon typically invest more into carceral interventions and less into therapeutic interventions.…”
Section: Discussionmentioning
confidence: 95%
“…Evidence suggests that these disparities may stem from racialized differences in perceptions of youth character, or latent criminality. For example, several studies have demonstrated that Black youth are stereotyped as “crime prone” and dangerous (Pickett and Chiricos 2012; Pickett et al 2014). Youth coming from areas of concentrated disadvantage are more likely to receive out-of-home placements, disproportionately affecting those who are Black and Hispanic (Rodriguez 2013).…”
Section: Racial Disparity In Juvenile Adjudicationsmentioning
confidence: 99%